Taḥlīl al-Kitāb al-Ta‘līmī al-Arabīyah Baina Yadai Aulādinā fī al-Juz al-Awwal li 'Abdi Al-Rahmān bin Ibrāhīm al-Fauzān wa Muhammad bin 'Abdi al Rahmān Ālu Syaikh min Nāhiyah al-Māddah - Wafa’ Az-Zahro; Zulham Effendi; Ade Muhammad Ritonga (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
This research aims to determine the suitability of al-Arabīyah Baina Yadai Aulādinā textbook material in the first volume by Abdurrahman bin Ibrahim Al-Fauzan and Muhammad bin Abdurrahman Alu Sheikh with the principles of preparing textbooks for non-Arabic speakers belonging to Nashir Abdullah Al-Ghali and Abdul Hamid Abdullah and with good book criteria in terms of material selection, material gradient, material presentation, and material repetition owned by Willia Francis Mackey. This research is library research with a content analysis method. The results of this research are, 1) generally, the teaching material of the first volume of the al-Arabīyah Baina Yadai Aulādinā book is following the principles of preparing textbooks for non-Arabic speakers. It is based on the requirements of social and cultural principles, the requirements of psychological principles, and the requirements of language and educational principles. 2) The teaching material of this book is following the characteristics of a good book by William Francis Mackey, namely based on the aspects of material selection, material gradient, material presentation, and material repetition. However, in the aspect of material selection, the analysis ofthe suitability of material selection based on learning objectives cannot be done because there are no learning objectives in the book.